EEG data of museum visitors experiencing visual and audiovisual simulations of Edzná, an archaeological site in MexicoOpenNeuro - Alonso-Valerdi Luz María; Rosado-Aíza Juan Pablo; Domínguez-Morales Fernando José; Pech-Canul Tania Yareni; Vázquez-Rodríguez Paola Guadalupe; Navas-Reascos Gustavo; Ibarra-Zárate David Isaac (Data in Brief)
This dataset contains electroencephalographic (EEG) recordings and user experience (UX) reports from 51 participants who experienced visual and audiovisual simulations of Edzná, a Mayan archaeological site in Mexico. Data were collected in two artistic environments: MOSTLA, a digital innovation lab at Tecnológico de Monterrey, and the Museum of Contemporary Art in Monterrey (MARCO). Participants were fitted with the Unicorn Hybrid Black EEG device and experienced the simulations through VR headsets and headphones. EEG data were recorded for three conditions: (1) baseline, (2) visual-only, and (3) audiovisual experiences. UX was assessed using the hedonic dimensions of the User Experience Questionnaire (UEQ), focused on stimulation and novelty scales. EEG data (both raw and preprocessed) are shared in the Brain Imaging Data Structure (BIDS) format and are openly available on OpenNeuro (https://openneuro.org/datasets/ds005628/versions/1.0.0). This dataset supports research in immersive technologies, neuroaesthetics, archaeoacoustics, and multisensory user experience evaluation.